Transcriptome analysis of Colletotrichum nymphaeae-Strawberry interaction reveals in planta expressed genes associated with virulence - Ozbudak, Egem; Carrillo-Tarazona, Yisel; Diaz, Edinson A.; Zambon, Flavia T.; Rossi, Lorenzo; Peres, Natalia A.; Raffaele, Sylvain; Cano, Liliana M. (Frontiers in Plant Science, 2025)
Colletotrichum nymphaeae, the causal agent of anthracnose fruit rot, is globally recognized as a major pathogen of strawberries due to its economic impact. Fungal pathogens utilize secreted proteins to facilitate infection by acquiring host nutrients and suppressing plant immunity. Understanding the transcriptomic responses of C. nymphaeae during infection can provide critical insights into its pathogenic mechanisms. In this study, RNA sequencing (RNA-seq) was performed to profile the transcriptome of C. nymphaeae strain 02-179 during infection of leaf and fruit tissues of the susceptible strawberry (Fragaria x ananassa) cultivar Florida Beauty. Differential gene expression analysis identified fungal genes upregulated during these interactions. Transcriptomic profiling revealed a set of genes encoding secreted effector proteins, including NUDIX hydrolase and LysM domain-containing proteins. Additionally, genes associated with Carbohydrate-Active enzymes (CAZymes), such as multicopper oxidase, pectinesterase, pectate lyase, glycosyl hydrolase family 7, and endochitinase, were significantly upregulated. Notably, two novel tannase genes were identified among the top upregulated genes in strawberry-infected leaves and fruits. Tannase enzymes are hypothesized to degrade tannins, a group of plant secondary metabolites abundant in strawberries, known for their defensive roles against pests and pathogens. The identification of tannase genes and the other genes associated with virulence underscores the complex molecular strategies employed by C. nymphaeae to infect and colonize strawberry tissues. Genes involved in degrading plant cell walls, suppressing host defenses, and potentially overcoming chemical barriers such as tannins play critical roles in the pathogenesis of anthracnose. Further functional characterization of these genes will enhance our understanding of the disease mechanisms and could inform the development of improved management strategies for C. nymphaeae infections in strawberries.